In fond memory of Yakov Borisovich Fainberg (Вопросы атомной науки и техники, 2005)
On March 7th, 2005, Yakov Borisovich Fainberg, the Academician of the National Academy of Science of Ukraine, passed away. The name of this notable scientist is inseparably linked with the developments in physics and technique of accelerators, nonrelativistic and relativistic plasma electronics, plasma physics and controlled fusion.